MINUMAN DAUN YACON SEBAGAI PRODUK UNGGULAN MASYARAKAT SENDURO - Leny Yuanita; Prima Retno Wikandari; Rinie Pratiwi; Wahyu Budi Sabtiawan; Dhita Ayu P.S (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
The target of the community service was the empowerment of the community of Argosari Village, Senduro to produce a ready-to-sell yacon leaf drink. This activity involved lecturers, students, farmer groups, and villagers. There were three stages in this activity, including preparation, implementation, and evaluation.The training included making yacon leaf drink and packaging of product. The community service were conducted for 8 months starting from February to September 2017. The product was a ready-to-sellyacon leaf drink with certificate number of P-IRT No. 2133508030333-22. In addition, the students have been able to socialize with Argosari Village community through yacon processing program and P -IRT permit arrangement.